Envelhecimento, Condições de Saúde e Atividades Físicas. - Moreira, Sérgio Augusto Silva Paredes (2016)
The growth of the elderly population has implications for different countries, since it is necessary to think about their social protection. During aging occur progressive and important physiological changes in organs and systems, such as reduced and altered muscle composition and bone mass; decreased cardiorespiratory capacity can impair the performance of various tasks, such as the simplest day-to-day. Characterized physical activity as any body movement due to the contraction of skeletal muscles held in different locations as work; moving on foot or by bicycle; in domestic and leisure activities. The objectives of the study were to identify the self reported diseases carried by the elderly; highlight the activities and relate such physical activities to self-reported diseases. Exploratory study of quantitative approach carried out with 480 elderly in the city of João Pessoa-PB, Brazil, of both sexes aged over 60 years. The sampling was probabilistic, by dual-stage conglomerate. Data collection was conducted through interviews in seniors' homes, between January 2011 and October 2011, after accepting participate and signed an informed consent form, the project was approved under No. 261 / 09 and FR: 294027. The data obtained from the interviews were organized into two databases prepared specifically for each instrument step by using SPSS 20.0 software. Among the investigated elderly, it was observed that physical activity is more prevalent in the age group between 60 and 69 years in women, married or in a stable relationship sex with income above two minimum wages and over five years of study. There was a predominance of married seniors with higher education to 5 years and earn up to two minimum wages. As for the distribution of activities by the elderly, comparing the two scenarios, one before the interview, that is, before 2011 and the other in the interview occasion there is an increase in purely domestic activities and a decrease in physical activity associated with a significant reduction in paid employment, which fell from 62.3% to 11.3%. As for the activities developed by the elderly before 2011 and during the interview, it appears that there was an increase in the exclusive performing household activities, reduced physical activity and paid work. Regarding self-reported diseases hypertension predominated in 59.5% of the elderly. Back problems and vision were mentioned by more than 40.0% of respondents, joint diseases by 30.6%. Regular physical activity benefits health, enhancing it in various aspects such as texture and quality muscle, improve balance, decrease in blood pressure, blood sugar and cholesterol, bone quality improvement and assists in psychological factors. The elderly acts of health promotion and maintenance are necessary for successful aging, with a good physical and mental health, in agreement with other studies.